Muscle pain induces task-dependent changes in cervical agonist/antagonist activity - Falla, D.; Farina, D.; Dahl, M. Kanstrup; Graven-Nielsen, T. (Journal of applied physiology (1985), 2007)
This study examined the effect of experimental neck muscle pain on the EMG-force relationship of cervical agonist and antagonist muscles. Surface EMG signals were detected from the sternomastoid, splenius capitis, and upper trapezius muscles bilaterally from 14 healthy subjects during cervical flexion and extension contractions of linearly increasing force from 0 to 60% of the maximum voluntary contraction (MVC). Measurements were performed before and after injection of 0.5 ml hypertonic and isotonic saline into either the sternomastoid or splenius capitis in two experimental sessions. EMG average rectified value (ARV) of the sternomastoid, splenius capitis, and upper trapezius muscles and the muscle fiber conduction velocity (CV) of the sternomastoid muscle were estimated at 5% MVC force increments. During cervical flexion with injection of hypertonic saline in sternomastoid, ARV of sternomastoid was lower on the side of pain in the force range 25–60% MVC ( P < 0.05) and was associated with a bilateral reduction of splenius capitis and upper trapezius ARV ( P < 0.01). During cervical extension, injection of hypertonic saline in splenius capitis resulted in lower estimates of splenius capitis ARV on the painful side from 45 to 60% MVC ( P < 0.05), which was associated with a bilateral increase in upper trapezius ARV estimates from 50 to 60% MVC ( P < 0.001). However, no significant change was identified for estimates of sternomastoid ARV. Experimentally induced neck muscle pain resulted in task-dependent changes in cervical agonist/antagonist activity without modifications in muscle fiber CV.